Spatial and temporal variation in vegetation land cover albedo in Finland - Safdari, Pezhman (Helsingfors universitet, 2015)
Surface albedo, which is the fraction of reflected radiant energy by earth’s surface to incoming solar energy, plays an important role in earth energy budget and energy equilibrium. Different features of the earth’s surface have different reflectivity rates which affect the albedo. Vegetation land-covers covering vast areas of earth’s surface as agricultural lands, forests, grass lands and so on, have great impact on land surface albedo. The Species composition, geographical distribution and seasonal phenology of different vegetation land-covers have an impact on surface albedo and consequently on earth’s energy budget and consequently, on climate change. Boreal zone covering latitudes between 60o – 70o N is one of the largest vegetation biomes on earth and which has a significant impact on surface albedo. The boreal region is mostly covered by coniferous forests which are optically very dark and absorb most of the incoming solar energy. This low reflectivity is very influential during the times that earth’s surface is snow covered by masking the high reflectivity of the snow covered land surface. This has caused most of the studies to focus on the boreal vegetation land-cover albedo during the snow covered periods of the year. In this study, the effect of five different vegetation classes (agriculture, broad leaves, coniferous, mixed forest and shrub lands) and the latitudinal gradient (northern, middle and southern Finland) and the vegetation phenology during the growing season on surface albedo of vegetated areas of Finland for the year 2009 has been investigated. The results of the study showed that there is a significant difference between the albedo of different vegetation land-cover classes. The albedo of agricultural lands tends to be systematically the highest in all conditions while conifers were the lowest. The vegetation land-cover albedo is generally lower in northern Finland compared to middle and south. There is a gradual increase in vegetation albedo until mid-July and after reaching a maximum ...